Experimental Study on Hydrodynamic Performance of the Integrated Floating Breakwater-Wind Turbine Device - Guo, Jianting; Wu, Renhao; Gao, Xubing; Yang, Yuxin (Shock and Vibration, 2023)
This study presents the design of an integrated floating breakwater-wind turbine device. The hydrodynamic performance was evaluated in a two-dimensional water tank under typical operating conditions to investigate its kinematic response and wave dissipation effect, while the original design was improved and optimized to enhance the overall performance of the integrated device. The improved integrated device had lower heave and sway motion amplitudes, better wave resistance, and better wave dissipation performance than the prototype. The improved integrated device can effectively reduce costs and optimize the allocation of resources by using a floating breakwater as a carrier for wind power generation and has broad application prospects.